Income Distribution and Consumption Deprivation: An Analytical Link - Mallick, Sushanta K. (Journal of Income Distribution®, 2008)
This article conceives poverty in terms of the consumption of essential food, makes use of a new deprivation (or poverty) function, and examines the effects of changes in the mean and the variance of the income distribution on poverty, assuming a log-normal income distribution. The presence of a saturation level of consumption can be treated as a poverty-line threshold as opposed to an exogenous income-based poverty line. Within such a consumption deprivation approach, the article proves analytically that rising mean income reduces poverty while rising variance of income distribution increases poverty.